2010
DOI: 10.1111/j.1537-2995.2009.02560.x
|View full text |Cite
|
Sign up to set email alerts
|

New antigen in the Dombrock blood group system, DOYA, ablates expression of Doa and weakens expression of Hy, Joa, and Gya antigens

Abstract: The patient's DO genes have a single-nucleotide change, which leads to the absence of the high-prevalence antigen DOYA. The absence of this antigen is associated with 183Asp and silencing of Do(a) and weakening of Gy(a), Hy, and Jo(a) antigens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Concerning the localization of the epitope recognized by MIMA‐53, it is interesting to note that the amino acid changes Tyr183Asp and Ile175Asn observed in DO*DOYA and DO*B‐(WL)‐I175N , respectively, are located only 7 amino acids apart in the same loop. A recent report based on results obtained using haemagglutination described a DO*DOYA ‐negative homozygous Turkish Kurd woman in whom the Tyr183Asp change silenced the expected Do a antigen and weakened Holley, Joseph, Gregory and DOMR antigens on RBCs (Mayer et al , ). Flow cytometry analysis showed that this probands' RBCs expressed the Do protein but to a lesser extent than control RBCs (MFI 424 vs. 845 with MIMA‐52) (Mayer et al , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the localization of the epitope recognized by MIMA‐53, it is interesting to note that the amino acid changes Tyr183Asp and Ile175Asn observed in DO*DOYA and DO*B‐(WL)‐I175N , respectively, are located only 7 amino acids apart in the same loop. A recent report based on results obtained using haemagglutination described a DO*DOYA ‐negative homozygous Turkish Kurd woman in whom the Tyr183Asp change silenced the expected Do a antigen and weakened Holley, Joseph, Gregory and DOMR antigens on RBCs (Mayer et al , ). Flow cytometry analysis showed that this probands' RBCs expressed the Do protein but to a lesser extent than control RBCs (MFI 424 vs. 845 with MIMA‐52) (Mayer et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Do a (DO1, International Society of Blood Transfusion [ISBT] reference 014001) and Do b (DO2, ISBT 014002), and a total of six high-incidence antigens, i.e. Gy a , Hy, and Jo a , plus the recently described DOYA, DOMR and DOLG antigens (Costa et al, 2010;Mayer et al, 2010;Karamatic Crew et al, 2011). These antigens are carried on the Dombrock glycoprotein (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58) that is attached to the red blood cell (RBC) membrane via glycosylphosphatidylinositol (GPI) linkage (Telen et al, 1990;Spring & Reid, 1991;Spring et al, 1994).…”
mentioning
confidence: 99%
“…Homology modelling predicted that Asp183 infl uences the formation or stability of the Cys182 -Cys123 disulphide bond [45] . She was homozygous for 547T > G in exon 2 of DO * A , encoding Tyr183Asp.…”
Section: Doya ( Do6) Domr ( Do7) and Dolg ( Do8)mentioning
confidence: 99%
“…One anti -Hy has been responsible for an HTR in a man who received two units of Hy + blood [35] . A man with anti -Gy a tolerated 10 units of Gy(a + ) blood with no adverse effect [63] and the patient with anti -DOYA was transfused with 3 units of incompatible blood, without evidence of reduced survival [45] . Anti -Hy was responsible for shortened in vivo red cell survival [36] and anti -Jo a in a sickle cell patient caused signifi cant removal of radiolabelled Jo(a + ) cells compared with Jo(a -) cells [64] .…”
Section: Antibodies To Other Dombrock Antigensmentioning
confidence: 99%
“…The Dombrock blood group system consists of two major antithetical antigens, Do a (DO1, International Society of Blood Transfusion [ISBT] 014001) and Do b (DO2, ISBT 014002), and several high‐incidence antigens, including Hy, Jo a , Gy a , DOYA, DOMR, DOLG, DOLC, and DODE …”
mentioning
confidence: 99%